Contribution of Alcohol and Nicotine Dependence to the Prevalence of Depressed Mood in Different Ethnic Groups in The Netherlands: The HELIUS Study. Issue 3 (2nd July 2020) - van Binnendijk, Simone; van Amsterdam, Jan G.C.; Snijder, Marieke B.; Schene, Aart H.; Derks, Eske M.; van den Brink, Wim
Abstract: Objective: Ethnic minorities report different levels of drinking and smoking and higher rates of depression compared to native populations. In this study we aimed to investigate in six ethnic groups whether tobacco and alcohol use were associated with depressive symptoms, which are more prevalent in ethnic minorities. Methods: Cross-sectional data from the multi-ethnic Healthy Life in an Urban Setting (HELIUS) study sample ( N  = 22, 471) was used, comprising 4, 580 native Dutch participants which were compared with participants from five ethnic minority groups (3, 259 South Asian Surinamese, 4, 292 African Surinamese, 2, 262 Ghanaian, 3, 891 Turkish, and 4, 187 Moroccan). Results: Alcohol misuse was positively associated with depressed mood in all ethnic groups except for the Dutch and the Ghanaians. Nicotine dependence was positively associated with depressed mood in all ethnic groups except for the Ghanaian group. Conclusions: Alcohol misuse and nicotine dependence were significantly associated with depressed mood in most but not all ethnic groups and especially in men. However, across all groups the contribution of alcohol misuse and nicotine dependence to depressed mood was small. Prospective multi-ethnic studies should confirm whether the relations are causal and elucidate their direction.